Impact of proximity of healthier versus less healthy foods on intake: A lab-based experiment. (1st February 2019) - Hunter, J.A.; Hollands, G.J.; Pilling, M.; Marteau, T.M.
Abstract: Background: Placing food further away from people decreases likelihood of consumption ("Proximity Effect"). However, it is unclear how proximity affects consumption when both healthier and less healthy foods are available and cognitive resource for self-control is limited. Aims: To test the hypothesis that when both healthier (raisins) and less healthy (chocolate M&Ms) foods are available, placing less healthy food far, rather than near, increases the likelihood that healthier food is consumed. Methods: General population participants ( N  = 248) were all put under cognitive load and randomised to one of four groups: 1. Raisins near (20 cm), M&Ms far (70 cm); 2. Both foods near; 3. M&Ms near, raisins far; 4. Both far. Primary outcome: proportions of participants consuming raisins and M&Ms, respectively. Results: The results did not support the primary hypothesis: when healthier and less healthy foods were both available, placing M&Ms far, rather than near, did not increase likelihood of consuming raisins ( OR  = 1.54, p  = .432). Regardless of the M&Ms proximity, likelihood of consuming raisins was unaffected by the raisins' proximity (62.9%(near) vs. 56.5%(far) OR  = 0.61, p  = .211). Likelihood of consuming M&Ms non-significantly decreased when they were far and raisins were near, and when both foods were far ( OR  = 2.83, p = .057). Likelihood of consuming M&Ms was affected by M&Ms proximity, being higher when near (68.3%) than far (55.6%), OR  = 0.39, p  = .015. Indices of cognitive load impact (higher vs lower) were unrelated to consumption of either food. Conclusions: Likelihood of consuming a healthier food was unaffected by its proximity and that of a less healthy food. By contrast, likelihood of consuming a less healthy food was influenced by its proximity and possibly by that of a healthier food. These effects need replication in studies designed to detect smaller effect sizes. Trial registration: This study was registered online with ISRCTN (ISRCTN11740813).